Pengujian Fitokimia dan Penentuan Kadar Senyawa Saponin Pada Ekstrak Etanol Bunga Telang (Clitoria ternatea L.) - Nugraha, Nyoman Dhamapada; Sukma Sanjiwani, Ni Made; Wahyu Udayani , Ni Nyoman (Fakultas Farmasi Universitas Mahasaraswati Denpasar, 2024)
Butterfly pea flower (Clitoria Ternatea L.) has long been used as a traditional medicine to cure various diseases so that it is used as a family medicinal plant (TOGA). Telang flower (Clitoria Ternatea L.) has properties as an antimicrobial, anthelmintic, or antiparasitic and insecticidal agent, fever medicine and pain reliever, anticancer, antioxidant, lowering blood sugar levels, anti-cholesterol, hypo-allergenic, immunomodulator and can be used in the treatment of wounds and can treat red eyes, tired eyes, skin diseases, and anti-toxins (Purba, 2020). This study aims to determine the presence or absence of saponins in the ethanol extract of butterfly pea and to determine the levels of saponins contained in the ethanol extract of butterfly pea (Clitoria Ternatea L.). A qualitative test was carried out by putting 0.5 gram of butterfly pea flower simplicia powder (Clitoria Ternatea L.) into a test tube, then adding 10 ml of hot water, shaking vigorously for 10 seconds and adding 2N HCl, then a quantitative test was carried out using the gravimetric method. Based on the research results that have been carried out positive butterfly pea flower extract (Clitoria Ternatea L.) contains saponin compounds with a saponin content of 1.54% using the gravimetric method. Keywords: Butterfly Pea Flower (Clitoria Ternatea L.), Saponins, Gravimetric Method.